Disentangling development of sensation seeking, risky peer affiliation, and binge drinking in adolescent sport. (March 2017) - Drane, Catherine Frances; Modecki, Kathryn L.; Barber, Bonnie L.
Highlights: Early levels of sensation seeking were related to early levels of binge drinking. Early levels of risky peers were related to early levels of binge drinking. Early high levels of sensation seeking predicted change in risky peers. Early high levels of sensation seeking predicted change in binge drinking. Change in binge drinking changed in tandem with change in risky peers.